Rancang Bangun Aplikasi Web Career Upgrade Bagi Calon Profesional dengan Metode Extreme Programming - Chusnia Dzurriati; Feri Wibowo; Agung Purwo Wicaksono; Ridho Muktiadi (Journal of Information System Research (JOSH), 2025)
The limitations of applications that can integrate job search features, Curriculum Vitae (CV) development and workshop training are the main drivers in the development of the Career Upgrade application. This study aims to create a web-based application that combines aspects of job search, Curriculum Vitae (CV) development and workshop training in one comprehensive system. The Extreme Programming (XP) method used in the development of the Career Upgrade Application has proven effective in producing an adaptive and responsive system. Extreme Programming (XP) has four stages, namely planning, design, coding, and testing. The Next.js framework is used as the basis for frontend development because of its speed and flexibility, while Firebase is used for data management. This study produces the Career Upgrade web application that integrates job search, Curriculum Vitae (CV) development, and workshop training in one application. The black-box testing technique is used in the development of the Career Upgrade Application, black-box testing carried out on the application shows that all main features function properly and shows that the application can operate effectively without any interference or errors. This application is expected to provide real contribution in providing comprehensive digital solutions for users who are looking for job vacancies, Curriculum Vitae (CV) development and workshop training.